Flood risk perception after indirect flooding experience: Null results in the German housing market - Nils aus dem Moore; Johannes Brehm; Philipp Breidenbach; Arijit Ghosh; Henri Gruhl (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
The frequency and severity of fluvial floods are expected to increase due to climate change. This paper investigates whether flood risk perception in the housing market changes across a country after the occurrence of a catastrophic fluvial flood. Using a comprehensive geocoded German house price data set and official flood risk maps, we exploit the July 2021 fluvial flood that was salient across Germany as an exogenous variation to causally measure the flood risk valuation update in a difference-in-differences setup. While we find that house prices decreased in the most inundated regions, no price changes occurred in flood risk regions that were not directly affected. This finding indicates that people did not update their risk perception after indirect exposure. With this paper, we contribute to the understanding of the impact of a salient flood on flood risk capitalization in places without direct exposure. – – Es ist zu erwarten, dass die Häufigkeit und Schwere von Flussüberschwemmungen aufgrund des Klimawandels zunehmen wird. In diesem Papier untersuchen wir, ob sich die Wahrnehmung des Hochwasserrisikos hinsichtlich des Wohnwerts in Risikogebieten auf dem Immobilienmarkt nach einem katastrophalen Hochwasser ändert. Unter Verwendung eines umfassenden geokodierten deutschen Hauspreisdatensatzes und offizieller Hochwasserrisikokarten nutzen wir das Hochwasser vom Juli 2021 als exogene Variation, um eine mögliche Neubewertung des Hochwasserrisikos in einem Differenz-in-Differenzen-Setup kausal zu messen. Wir stellen fest, dass die Hauspreise zwar in den direkt betroffenen Regionen gesunken sind. In den bei dieser Flut nicht direkt betroffenen Hochwasserrisikogebieten zeigt sich allerdings keine Preisveränderungen. Dieses Ergebnis deutet darauf hin, dass die Menschen ihre Risikowahrnehmung nach einer indirekten Betroffenheit nicht aktualisiert haben, obwohl das gestiegene Risiko für die indirekt Betroffenen in gleicher Weise veranschaulicht wurde.
Keywords: Q54; Q51; D81; R31; 330; Flood risk; home prices; risk updating